Kearifan Lokal Masyarakat Suku Dayak Iban Dalam Konservasi Burung Di Desa Mungguk Gelombang : Local Wisdom of the Dayak Iban Ketungau Community in Bird Conservation in Mungguk Gelombang Village - Eduardus Julio Egi; Nasfiatun (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
ABSTRACTS Birds have an important role in an ecosystem, especially in the process of seed dispersal and forest regeneration. Climate change and anthropogenic influences in the form of forest conversion to non-forest are very real threats to bird species. Information in the form of knowledge or local wisdom of the community is an important factor in supporting bird conservation activities. This study aims to identify local wisdom of the community and its role in bird conservation in Mungguk Gelombang Village. The data collection technique in this study used an in-depth interview method with respondents determined using the snowball sampling technique. The data obtained were analyzed qualitatively descriptively. The results of the study showed that the Mungguk Gelombang Village Community has local wisdom in the form of seven species of birds that are considered to have magical values known as tujuh burung pemali. These seven birds are not allowed to be hunted because they are believed to bring bad luck. This makes the seven species of birds included in the list of tujuh burung pemali remain preserved in their natural habitat. KEYWORDS